Individual impression technique by using functional method on the custom ocular prosthesis: a case report - Ervi Gani; Ricca Chairunnisa; Haslinda Z. Tamin (Indonesia Prosthodontic Association, 2022)
Enucleation leads to contracture of orbital tissue accompanied by reduction in volume and forniceal depth, which results in an inability to sustain a prosthesis. Shallow inferior fornix in contracted eye socket compromises adaptati-on, retention, stabilization and duplication of palpebral opening similar to natural eye in terms of size, support, con-tour and convexity make fabrication of custom ocular prosthesis become challenging. Hence, the present article describes the use of ocular prosthesis as conformer to obtain better appearance and enlarge orbital dimension in contracted socket. A 21-year-old male came to Dental Hospital Universitas Sumatera Utara with a complaint of un-aesthetic face appearance due to enucleation of left eye in the last 5 years old subsequent to trauma by sharp blades. The patient had already used an ocular prosthesis but lost it 6 years ago and didn’t used it until now. In cli-nical examination, the anopthalmic socket had good posterior wall mobility and absence of infection but, mild con-tracted socket (Grade 1) with shallow inferior fornix depth was examined. In this case, ocular prosthesis provides aesthetics as well as expanding the lid anteriorly, conjunctiva and fornix posteriorly that were successfully obtain-ed by performing functional impression using imprinted waxed up. This results in a favorable peripheral eye seal.